Bildung und Liebe: Interdisziplinäre Perspektiven - Sojer, Thomas; Steinmair-Pösel, Petra; Köffler, Nadja; Stöger, Peter (transcript, 2018)
What is education if it isn't the question about the human being? Yet what does a concept of education mean that totally dispenses with what we call love? This book makes the case for re-consideration.